Defect structure and strain reduction of 3C-SiC/Si layers obtained with the use of a buffer layer and methyltrichlorosilane addition. Issue 15 (29th March 2016) - Bosi, M.; Attolini, G.; Negri, M.; Ferrari, C.; Buffagni, E.; Frigeri, C.; Calicchio, M.; Pécz, B.; Riesz, F.; Cora, I.; Osváth, Z.; Jiang, L.; et al.
Abstract : 3C-SiC layers were deposited on Si substrates by using a low temperature buffer layer and the addition of methyltrichlorosilane (MTS) to the gas phase during the high temperature thick film growth. Abstract : 3C-SiC layers were deposited on Si substrates by using a low temperature buffer layer and the addition of methyltrichlorosilane (MTS) to the gas phase during the high temperature thick film growth. Several samples were grown by varying the deposition temperature and the MTS content in order to study how these parameters affect the layer quality and the lattice defects. All of the grown layers are single crystalline and epitaxial to the substrate. The formation of empty voids at the SiC/Si interface was successfully avoided. The surface of the layers grown with MTS addition was smoother and contained less residual strain. A 15 μm thick 3C-SiC sample was grown using an optimized process in order to evaluate its residual strain and bow.